2019
DOI: 10.1002/app.48310
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic morphology, rheological behavior, and mechanical properties of polymers: Recycled acrylonitrile‐butadiene‐styrene/polybutylene terephthalate blends

Abstract: In this study, styrene‐acrylonitrile‐glycidyl methacrylate (SAG) series copolymers were specially designed for producing the recycled acrylonitrile‐butadiene‐styrene (rABS)/poly(butylene terephthalate) (PBT)/SAG blends, which were prepared through the process of continuous melt blending and batch feeding. The effects of viscosity composition, SAG chemical composition, and SAG content on the morphology, and rheological and mechanical properties of the blends have been investigated. As demonstrated by morphologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…As depicted in Figure 6(a), composites with higher loading of POE‐g‐MAH present higher G' values along the whole testing frequency. With the addition of POE‐g‐MAH, the linear platform of the storage modulus has been expanded, which indicates that the interaction of the phase interface in the blend is improved 48 . This phenomenon also suggests the addition of POE‐g‐MAH improves the compatibility between the inorganic particles and matrix, which increases the stiffness of the composite material and can store more energy under the action of external force.…”
Section: Resultsmentioning
confidence: 90%
“…As depicted in Figure 6(a), composites with higher loading of POE‐g‐MAH present higher G' values along the whole testing frequency. With the addition of POE‐g‐MAH, the linear platform of the storage modulus has been expanded, which indicates that the interaction of the phase interface in the blend is improved 48 . This phenomenon also suggests the addition of POE‐g‐MAH improves the compatibility between the inorganic particles and matrix, which increases the stiffness of the composite material and can store more energy under the action of external force.…”
Section: Resultsmentioning
confidence: 90%
“…In addition, we observed the fracture surface at a higher magnification. It is found that there are many filamentous structures on the impact surface of 0215H, which is due to the high interfacial strength of the PB phase and the SAN phase at fracture . For 0215H-1,0215H-3, and 0215H-5, many smooth holes appear on the fracture surface, circled in Figure , which is caused by the PB phase being directly pulled out from the SAN phase, and the number of holes increases with the increase of cycles of FDM.…”
Section: Results and Discussionmentioning
confidence: 95%
“…It is found that there are many filamentous structures on the impact surface of 0215H, which is due to the high interfacial strength of the PB phase and the SAN phase at fracture. 30 For 0215H-1,0215H-3, and 0215H-5, many smooth holes appear on the fracture surface, circled in Figure 6, which is caused by the PB phase being directly pulled out from the SAN phase, and the number of holes increases with the increase of cycles of FDM. This indicates that after cycled FDM, the way of fracture changes, and the interface strength of the PB phase and the SAN phase decreases significantly, and the interface strength decreases more obviously with the increase of cycles of FDM.…”
Section: Morphology Of the Fracture Surfacementioning
confidence: 99%
“…On the other hand, ABS has also some drawbacks, especially for high‐performance applications, such as poor solvent, fatigue, and UV resistance, lower HDT/Vicat temperature, and impact resistance than high‐performance engineering plastics. In this context, blends of ABS with other engineering thermoplastics such as polycarbonate (PC), [ 18,19 ] polyamides (PA), [ 20,21 ] polybutylene terephthalate (PBT), [ 22,23 ] and styrene–acrylonitrile [ 24,25 ] are of significant scientific and commercial interest. In blending efforts of ABS and high‐performance engineering thermoplastics, ABS provides ease of processability and reliable notched impact resistance, [ 26,27 ] whereas other engineering thermoplastics improve mechanical, thermal and energy absorption properties.…”
Section: Introductionmentioning
confidence: 99%